PENGARUH RELATIONSHIP MARKETING TERHADAP CUSTOMER RETENTION ORIENTATION NASABAH BANK SYARIAH DI KOTA MALANG - Hasan, MM,, Irmayanti (Fakultas Ekonomi, UIN Maliki Malang, 2008)
The increasing stringency emulation at banking industry, especially the islamic banking industry, brings the importance of relationship improvement between islamic banks with their costumers. By using relationship marketing as one of the key action to reach costumers’ retention orientation, this research aims to analyze the direct influences, both simultaneously and partially, of variables: belonging, communication, customization, differentiation, personalisation and security, and convinience to costumers’ retention orientation of islamic banks in Malang. The samples are taken from two islamic bank branches in Malang, those are: PT. BRI SYARIAH MALANG BRANCH and PT. BTN SYARIAH MALANG BRANCH. This research applies the quantitative approach, by means of the surveys to take samples from the population, and questionaires to collect the principal data. Number of samples is determined by Slovin’s formula with proportional sampling method to each population: 65 customers of PT. BRI SYARIAH MALANG BRANCH and 35 customers of PT. BTN SYARIAH MALANG BRANCH. Multiple regression analysis is used to predict the relationship between variables. Hypothetic test using F test indicates that the significant simultaneous influence of relationship marketing variables; those are belonging (X1), communication (X2), customization (X3), differentiation (X4), personalization (X5), and security and convenience (X6) to customers’ retention orientation (Y) is acceptable. The test partially indicates that the significant influence of belonging (X1), communication (X2), and customization (X3) to customers’ retention orientation (Y) is acceptable, while the significant influence of differentiation (X4), personalization (X5), and security and convenience (X6) is unacceptable.